Bryde’s whale (Balaenoptera edeni) new record for mainland Portugal - Castro, Joana; Cid, André; Laborde, Marina I (J. Cetacean Res. Manage., 2021)
Brydes’s whale (Balaenoptera edeni) is a species of baleen whale known to live year-round in warm waters, although the distribution of the species in the North Atlantic Ocean is still poorly known. In this work we report the sighting of an adult individual during the summer of 2020 in the South coast of Portugal. The whale was observed 6.4 nautical miles from the shore at a depth of 50.6 metres. Initially this individual was associated with a group of bottlenose dolphins. This is the first record of this species for mainland Portugal.